Management for deans - Friel, Terri (Emerald Publishing Limited : IAP, Information Age Publishing, Inc., 2013)
Are you considering a dean's position? Are you a new dean? Are you a sitting dean that would like some ideas on managing your organization? This book offers advice and important information for anyone working at the dean's level in academic administration. Written in a conversational tone and organized by major topics such as Managing Faculty, Students, Strategic Planning, etc, this book will inform anyone about the many tasks required of a dean as well as provide advice on how to do them well.This book was written by Dr. Terri Friel, an administrator for 7 years. She worked as an engineer and managed production at Procter and Gamble and Pepsico and applies this management experience and knowledge as well as her Doctorate studies in Engineering Management to develop a good overview of the job of Dean. While there are general books written about the topic of academic administration, this is one of the only books that specifically addresses the issues of being a dean. If you just think you want to be a dean or are working as a dean currently, this book will be a helpful guide and reference for you.